2016
DOI: 10.1007/s40271-016-0205-9
|View full text |Cite
|
Sign up to set email alerts
|

Is Financial Literacy a Determinant of Health?

Abstract: Changes in economic conditions and healthcare delivery models have shifted more healthcare costs to patients, resulting in greater patient financial responsibilities. As a result, it is important to understand the potential impact of financial literacy on patients' healthcare behavior. With the focus on delivering better health outcomes at lower costs, factors that influence patient behavior are important considerations for healthcare providers. Although researchers have proposed a variety of conceptual models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 50 publications
0
9
0
2
Order By: Relevance
“…Empirical evidence indicates that 70% of consumers diagnosed with cancer reduce leisure activities, 48% withdraw savings and 18% sell their possessions (De Souza et al, 2014). Moreover, out-of-pocket cost of treatment often forces consumers with chronic disease and low income to reduce expenditure on food and even medication, which exacerbates their health problems (Galbraith et al, 2011;Ubel et al, 2013;Kullgren and Mclaughlin, 2010;Meyer, 2017). Another consequence of high financial distress might be foregoing the medical care completely or switching from a more effective to a less effective therapy.…”
Section: Financial Literacy and Quality Of Lifementioning
confidence: 99%
“…Empirical evidence indicates that 70% of consumers diagnosed with cancer reduce leisure activities, 48% withdraw savings and 18% sell their possessions (De Souza et al, 2014). Moreover, out-of-pocket cost of treatment often forces consumers with chronic disease and low income to reduce expenditure on food and even medication, which exacerbates their health problems (Galbraith et al, 2011;Ubel et al, 2013;Kullgren and Mclaughlin, 2010;Meyer, 2017). Another consequence of high financial distress might be foregoing the medical care completely or switching from a more effective to a less effective therapy.…”
Section: Financial Literacy and Quality Of Lifementioning
confidence: 99%
“…The consequences of financial burden due to out‐of‐pocket expenditures for people who undergo bariatric surgery (and indeed other disease categories across different health care systems) are poorly understood (Aji, Yamamoto, & Sauerborn, ; Campbell, Venn, et al, ; Gott, Allen, Moeke‐Maxwell, Gardiner, & Robinson, ; Timmons, Gooberman‐Hill, & Sharp, ; Ubel, Abernethy, & Zafar, ; Wu, Odisho, Washington, Katz, & Smith, ). A recent study has found that financial distress is a key determinant of health (Meyer, ).…”
Section: Discussionmentioning
confidence: 99%
“…This may be related to the fact that younger adults and females have lower levels of knowledge about financial literacy and how to finance their medical care (Fonseca, Mullen, Zamarro, & Zissimopoulos, 2012; Karpman & Caswell, 2017). Financial education programs to increase individuals’ financial literacy in the context of health care would promote better financial behaviors in relation to health service utilization (Meyer, 2017).…”
Section: Discussionmentioning
confidence: 99%